'Not a heap of stones': material environments and ontological security in international relations*. Issue 1 (2nd January 2017) - Ejdus, Filip
Abstract: Extant scholarship on ontological security in international relations has focused on the significance of social environments for state identity. In this article, I argue that material environments also provide an important source of ontological security for states. In order to assume this role material environments need to be discursively linked to state identity through either projection or introjection. Once incorporated into state identity narratives, material environments become 'ontic spaces': spatial extensions of the collective self that cause state identities to appear more firm and continuous. However, ontic spaces are inherently unstable and require maintenance, especially during periods of crisis or transition. States bear agency in this process but they never achieve full control, as identity discourses are continuously contested both domestically and internationally. I illustrate these claims by looking at the role of the General Staff Headquarters in Belgrade, destroyed by the North Atlantic Treaty Organization in 1999, in the ontological security of Serbia.